2004
DOI: 10.1038/nsmb862
|View full text |Cite
|
Sign up to set email alerts
|

Human CD59 is a receptor for the cholesterol-dependent cytolysin intermedilysin

Abstract: Cholesterol is believed to serve as the common receptor for the cholesterol-dependent cytolysins (CDCs). One member of this toxin family, Streptococcus intermedius intermedilysin (ILY), exhibits a narrow spectrum of cellular specificity that is seemingly inconsistent with this premise. We show here that ILY, via its domain 4 structure, binds to the glycosyl-phosphatidylinositol-linked membrane protein human CD59 (huCD59). CD59 is an inhibitor of the membrane attack complex of human complement. ILY specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
255
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(270 citation statements)
references
References 39 publications
12
255
2
1
Order By: Relevance
“…Domain 4 also participates in the binding of hCD59 to C8a and C9. 30,33 We have consistently demonstrated that rILYd4 specifically abrogates hCD59 function in both normal human cells and B lymphoma cells. Furthermore, we demonstrated that rILYd4 (IC 50 533 nM) restores the sensitivity of a rituximabresistant NHL cell line to the rituximab CDC effect.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Domain 4 also participates in the binding of hCD59 to C8a and C9. 30,33 We have consistently demonstrated that rILYd4 specifically abrogates hCD59 function in both normal human cells and B lymphoma cells. Furthermore, we demonstrated that rILYd4 (IC 50 533 nM) restores the sensitivity of a rituximabresistant NHL cell line to the rituximab CDC effect.…”
Section: Introductionmentioning
confidence: 86%
“…The receptor for ILY is specific for hCD59. 30,31 Using the generation of different mutant ILYs, LaChapelle et al recently demonstrated that the ILY-hCD59 interaction during the assembly of the pore complex increases host cell susceptibility to the CDC effect. 32 Domains 1-3 of ILY are responsible for pore formation, while domain 4 binds to amino acids 42-58 in hCD59.…”
Section: Introductionmentioning
confidence: 99%
“…This is often achieved by one or more mechanisms such as regulated secretion (perforin), 3 proteolytic activation (perforin), 3 pH sensitivity (LLO, perforin), 3,25 receptor specificity to target membranes (intermedilysin) 36 or the presence of immunity proteins on non-target membranes (complement MAC). 37 How apicomplexan parasites prevent autolysis by ApiPLPs following secretion remains an interesting area deserving of additional work.…”
Section: Discussionmentioning
confidence: 99%
“…A good example is the intermedilysin (ILY) of Streptococcus intermedius which recognises CD59, an GPI-anchored protein, as the membrane receptor although it has been classified as a cholesterol-dependent cytolysin (Giddings et al 2004). a-hemolysin of In summary, by a combination of affinity purification and SILAC-based quantitative mass spectrometry we have identified the folate receptor alpha as an interaction partner of HALT-1.…”
Section: Discussionmentioning
confidence: 99%
“…A few bacterial pore-forming toxins have been proven to bind proteinaceous receptors in addition of their affinity to membrane lipids (Dal Peraro and van der Goot 2016; DuMont and Torres 2014). These pore-forming toxins include the intermedilysin (ILY) of Streptococcus intermedius which recognises CD59, an GPI-anchored protein, as the membrane receptor although it has been classified as a cholesterol-dependent cytolysin (Giddings et al 2004). Hence, membrane proteins can be potential candidates as receptors for HALT-1.…”
Section: Introductionmentioning
confidence: 99%